ANALISIS PENGARUH PEMBERIAN FASILITAS KITE (KEMUDAHAN IMPOR TUJUAN EKSPOR) DAN NILAI TUKAR RUPIAH TERHADAP NILAI EKSPOR DI JAWA TENGAH - Ismaida - Pratiwi; Sugiyanta - Sugiyanta; Agus - Suratno (Admisi dan Bisnis, 2015)
This research examines the influenceKITEfacilities and Rupiah exchange rate to exportvalues in Central Java using the monthly datafrom January 2006 until December 2011usessecondary data from some governmentinstance in Central Java, and using themultiple linier regression analysis by SPSSversion 16.0.The objective of this research is to analysis ofinfluence KITE facilities and Rupiahexchange rate to export values in CentralJava.The results simultaneous by F-test indicatedthat the present KITE facilities and Rupiahexchange rate affected export values inCentral Java significantly. Meanwhile, theresult of this research in partial (T-test)indicated that the present KITE facilitiesaffected positivelyand significantly towardexport values. While Rupiah exchange rateaffect negatively significantlytoward exportvalues in Central Java